Limited Effects of Endurance or Interval Training on Visceral Adipose Tissue and Systemic Inflammation in Sedentary Middle-Aged Men - Joshua H. F. Cooper; Blake E. G. Collins; David R. Adams; Robert A. Robergs; Cheyne E. Donges (Hindawi Limited, 2016)
Purpose. Limited data exists for the effects of sprint-interval training (SIT) and endurance training (ET) on total body composition, abdominal visceral adipose tissue, and plasma inflammation. Moreover, whether "active" or "passive" recovery in SIT provides a differential effect on these measures remains uncertain. Methods. Sedentary middle-aged men (n=62; 49.5±5.8 y; 29.7±3.7 kg·m2) underwent abdominal computed tomography, dual-energy X-ray absorptiometry, venepuncture, and exercise testing before and after the interventions, which included the following: 12 wks 3 d·wk−1 ET (n=15; 50-60 min cycling; 80% HRmax), SIT (4-10 × 30 s sprint efforts) with passive (P-SIT; n=15) or active recovery (A-SIT; n=15); or nonexercise control condition (CON; n=14). Changes in cardiorespiratory fitness, whole-body and visceral fat mass, and plasma systemic inflammation were examined. Results. Compared to CON, significant increases in interpolated power output (P-SIT, P<0.001; ET, P=0.012; A-SIT, P=0.041) and test duration (P-SIT, P=0.001; ET, P=0.012; A-SIT, P=0.046) occurred after training. Final VO2 consumption was increased after P-SIT only (P<0.001). Despite >90% exercise compliance, there was no change in whole-body or visceral fat mass or plasma inflammation (P>0.05). Conclusion. In sedentary middle-aged men, SIT was a time-effective alternative to ET in facilitating conditioning responses yet was ineffective in altering body composition and plasma inflammation, and compared to passive recovery, evidenced diminished conditioning responses when employing active recovery.